South Africa's democracy at the crossroads - Silander, Daniel; Silander, Charlotte; Elst, Herman van der; Heydenrych, Pieter (Bingley, U.K. : Emerald Publishing Limited, 2022)
Since the first elections of 1994, the South African constitution officially guarantees and promotes a wide range of political and civil rights and institutionalizes the separation of powers with an independent judiciary. This has made South Africa a political symbol of change, hope and democracy in Africa and around the world. However, since the introduction of free and fair electoral processes and with ANC dominating the presidency and the parliamentary seats, the political scene has been scattered by democratic challenges. South Africa remains a flawed democracy, combining free elections and respect for basic civil liberties with problems of governance, an underdeveloped political culture, and low levels of public participation. Today, South Africa stands at a crossroads. While the constitutional democracy has survived, South African democracy seems to have weakened by state capture, internal ANC implosion, corruption, societal polarization, social exclusion, xenophobia, and threats of state economic bankruptcy. South Africa faces growing discontent symbolized in intensified societal and political debates, protests and demonstrations providing for the question if this is a sign of dissatisfied citizens demanding deeper democracy or activities questioning the established constitutional democracy from an anti-democratic, populist, and radical point of view. South Africas Democracy at the Crossroads explores the question; what are the challenges to future democratization in South Africa?
Chapter 1. Democracy at the crossroads: The case of South Africa / Daniel Silander and Oskar Malmgren -- Chapter 2. Challenges to democracy: A framework of analysis / Daniel Silander -- Chapter 3. The politics of apartheid in South Africa: 1910-1994 / KGame Molope -- Chapter 4. Political society: Challenges and opportunities for democratic consolidation / Martin Nilsson -- Chapter 5. Bureaucratic society liberalism and liberationism: Institutional compromises and bureaucratic management / Piet Croucamp -- Chapter 6. Judicial society: Constitutionalism and the rule of law / Pieter Heydenrych -- Chapter 7. Economic society: A stable economic society as a requirement for successful democratic consolidation in South Africa / Herman van der Elst -- Chapter 8. Civil society: Exploring the democratic role of popular protests / Gideon van Riet and Daniel Silander -- Chapter 9. Safety and security society: Security infrastructures and democracy in a context of negative peace / Gideon van Riet -- Chapter 10. Educational society: Education as prerequisite for social cohesion / Charlotte Silander -- Chapter 11. Sport society: The role of sport and identity in democratic society / Emma Ricknell -- Chapter 12. The international society: Global and regional decline of democracy / Daniel Silander and Prince Simunkombwe -- Chapter 13. Contemporary challenges to South African democracy / Daniel Silander.
Includes index.
Keywords: Democracy -- South Africa; Political Science -- Political Ideologies / Democracy; Political structures: democracy